Conservation Subdivision: Post-construction Phase-Engaging Residents - Daniel Feinberg; Mark Hostetler (EDIS)
As urban communities grow, design and management strategies for new developments become critical factors that determine impacts on natural resources. How can we accommodate growth yet conserve natural resources, such as biodiversity, water, and energy? In this document, we focus on conserving biodiversity when land is subdivided, constructed, and occupied. This 6-page fact sheet was written by Daniel Feinberg and Mark Hostetler and published by the UF Department of Wildlife Ecology and Conservation, June 2013.